2001
DOI: 10.4319/lo.2001.46.2.0309
|View full text |Cite
|
Sign up to set email alerts
|

Composition and cycling of marine organic phosphorus

Abstract: Using tangential-flow ultrafiltration and solid-state 31 P nuclear magnetic resonance (NMR) spectroscopy, the dominant compound classes of marine high-molecular weight (1-100-nm size fraction) dissolved organic phosphorus (DOP) have been characterized in 16 samples from the Pacific Ocean, the Atlantic Ocean, and the North Sea. NMR spectra of ultrafiltered dissolved organic matter (UDOM) from all sites and depths reveal that P esters (75%) and phosphonates (25%) are the major components of ultrafiltered DOP (UD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
258
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(283 citation statements)
references
References 51 publications
18
258
1
3
Order By: Relevance
“…Phosphonates have recently been recognized as a potential source of phosphorus in oligotrophic systems (Kolowith et al, 2001). These compounds, which contain a C-P bond, are particularly stable and are thought to mainly originate from eukaryotic lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphonates have recently been recognized as a potential source of phosphorus in oligotrophic systems (Kolowith et al, 2001). These compounds, which contain a C-P bond, are particularly stable and are thought to mainly originate from eukaryotic lipids.…”
Section: Discussionmentioning
confidence: 99%
“…[107] Quantification There are few studies that have quantified phosphonates (as a broad class of compounds) in aquatic samples, and in those studies that have it appears that the relative importance of phosphonates to the total P pool is quite variable. 31 P NMR studies have shown that phosphonates account for between 5 [108] and 25 % [109] of the dissolved organic phosphorus pool Organic P in the aquatic environment in marine samples -with most of the phosphonates associated with the high molecular weight fraction. [109] Phosphonates in marine particulate matter seems more variable.…”
Section: Phosphonatesmentioning
confidence: 99%
“…31 P NMR studies have shown that phosphonates account for between 5 [108] and 25 % [109] of the dissolved organic phosphorus pool Organic P in the aquatic environment in marine samples -with most of the phosphonates associated with the high molecular weight fraction. [109] Phosphonates in marine particulate matter seems more variable. Benitez-Nielsen et al [110] report that phosphonates account for between 3 and 18 % of the total P in sediment traps deployed in the Cariaco Basin, with the lowest values found in the deepest (1255 m) traps.…”
Section: Phosphonatesmentioning
confidence: 99%
“…For instance, phosphonates (Phns) appear to constitute a significant fraction of dissolved organic P in the oceans. In parts of the Pacific Ocean, Phns can constitute as much as 25% of the dissolved, high-molecularweight organic P (Clark et al, 1998;Kolowith et al, 2001) although the exact source of the Phns is not known. Phns can be components of membrane phosphonolipids, nucleic acids, proteins and polysaccharides (Kononova and Nesmeyanova, 2002).…”
Section: Introductionmentioning
confidence: 99%